Canadian integrative oncology research priorities: results of a consensus-building process - Weeks, L.C. (Multimed Inc., 2013)
BACKGROUND: In Canada, many diverse models of integrative oncology care have emerged in response to the growing number of cancer patients who combine complementary therapies with their conventional medical treatments. The increasing interest in integrative oncology emphasizes the need to engage stakeholders and to work toward consensus on research priorities and a collaborative research agenda. The Integrative Canadian Oncology Research Initiative initiated a consensus-building process to meet that need and to develop an action plan that will implement a Canadian research agenda. METHODS: A two-day consensus workshop was held after completion of a Delphi survey and stakeholder interviews. RESULTS: Effectiveness. Safety. Resource and health services utilization. Knowledge translation. Developing integrative oncology models. Research is needed within each priority area from a range of different perspectives (for example, patient, practitioner, health system) and in a way that reflects a continuum of integration from the addition of a single complementary intervention within conventional cancer care to systemic change. Strategies to implement a Canadian integrative oncology research agenda were identified, and working groups are actively developing projects in line with those strategic areas. Of note is the intention to develop a national network for integrative oncology research and knowledge translation. CONCLUSIONS: The identified research priorities reflect the needs and perspectives of a spectrum of integrative oncology stakeholders. Ongoing stakeholder consultation, including engagement from new stakeholders, is needed to ensure appropriate uptake and implementation of a Canadian research agenda.